Implementation of a Web-Based Online Registration System for Extracurricular Activities at State Vocational School 72 Jakarta - Sarimole, Frencis Matheos; Betty Yel, Mesra; Iqhlima, Salabila Listania; Sidiq, Bagas Maulana; Hidayati, Siti Nur; Bere Tae, Chelvyn Erikson (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study proposes a web-based extracurricular registration system to improve the effectiveness of student activity management at SMK Negeri 72 Jakarta. Currently, the extracurricular registration process is still conducted manually using paper forms, which often causes problems such as slow data processing, data recording errors, limited information access, and ineffective promotion of activities. To address these issues, this research designs a digital registration platform that allows students to view extracurricular information, register online, and monitor registration status easily. The system also provides administrative features for managing extracurricular data, validating student registrations, organizing schedules, and generating reports. Two main user roles are implemented, namely students and administrators. The proposed system is expected to support a faster, more accurate, and more transparent registration process. By adopting this web-based approach, the school can reduce administrative workload, improve service quality, and enhance student participation in extracurricular programs. The proposed system is therefore considered beneficial in supporting school digital transformation and student development activities.